Pengaruh Pengembangan Sumber Daya Manusia Dan Human Relations (Hubungan Antar Manusia) Terhadap Kinerja Karyawan Badan Pengawas Obat dan Makanan Kota Medan - Aji Pangestu; Muhammad Yamin Siregar; Isnaniah Lailikhatmisafitri (Universitas Medan Area, 2020)
The purpose of this study was to determine the effect of the development of human resources partially on the performance of employees at the Office of Drug and Food Supervisor of Medan City. For the influence of the development of human resources and human relations simultaneously on the performance of employees at the Office of Drug and Food Supervisor of Medan City. The population in this study were 115 employees of the Center for Drug and Food Control of Medan City, using a sample of 89 permanent employees. To obtain data in the preparation of this thesis, the author uses the instrument; documentation study and interview (interview), and questionnaire (questionnaire). In analyzing the data using multiple linear regression, t test, F test and determination test. Based on the results of the partial test (t test) it can be concluded that the development of human resources has a significant influence on employee performance. Human relations has a significant influence on employee performance. Based on the results of the F test, it can be concluded that the variables of human resource development and human relations together have a significant effect on employee performance. The R-Square value obtained is 0.981 indicating that around 98.1% of the Y variable (employee performance) can be explained by human resource development variables (X1) and human relations variables (X2). The remaining 1.9% is influenced by other variables.Keywords: Human Resource Development, Human Relations and Performance